The Effectiveness of Problem Solving Based Student Worksheets in Improving Elementary School Students’ Computational Thinking Skills A Gender Perspective Analysis to Support the Achievement of SDGs 5 - Rafi Afrizal Saputra; Zaenal Abidin; Wiryanto Wiryanto; Ramadhan Kurnia Habibie (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study aims to determine the effectiveness of problem-solving-based Student Worksheets in improving the computational thinking skills of fourth-grade elementary school students on the topic of fractions. This study employs a pre-experimental method with a quantitative approach using a One Group Pretest–Posttest Design. The research subjects consisted of 23 fourth-grade students at SDN Sonokwijenan II/96. Data were collected through questionnaires as well as pretest and posttest instruments. The results showed a significant improvement in students’ computational thinking skills, with the average score increasing from 40 on the pretest to 65.32 on the posttest. The paired t-test results showed a significance value of 0.001 < 0.05, indicating a statistically significant difference. The N-Gain score was 0.42, which falls into the moderate category, and Cohen’s d effect size was 1.180, indicating a very strong effect. These findings indicate that the developed problem-solving-based worksheets meet the criteria of being valid, practical, and effective in enhancing students’ conceptual understanding and learning outcomes in fractions. These worksheets are designed to systematically integrate problem-solving stages, thereby helping students understand problems, formulate solution strategies, and evaluate the results obtained. Furthermore, the use of problem-solving-based worksheets provides a more meaningful learning experience as students are actively engaged in the learning process and encouraged to think logically and systematically when solving mathematical problems.